2023
DOI: 10.3390/plants12102037
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Mepiquat Chloride Regulating Soybean Response to Drought Stress Revealed by Proteomics

Shoukun Dong,
Xin Wang,
Xiaomei Li
et al.

Abstract: Soybeans are the main sources of oil and protein for most of the global population. As the population grows, so does the demand for soybeans. However, drought is a major factor that limits soybean production. Regulating soybean response to drought stress using mepiquat chloride (MC) is a feasible method; however, its mechanism is still unclear. This study used PEG-6000 to simulate drought stress and quantitative proteomic techniques to reveal changes in Heinong44 (HN44) and Heinong65 (HN65) subjected to drough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The PPI is involved in almost all the important biological processes within the living body and play a crucial role in the fundamental life processes of the cell [30]. Highly aggregated proteins often exhibit similar functions [31], while proteins with a high degree of connectivity may be key points for influencing metabolic reactions [27]. The DEPs in each comparison group were compared with the STRING database, and protein interaction network maps were drawn by screening the proteins with closer interactions (Figures 8-11).…”
Section: Ppi Network Analysis Of Deps In Different Samplesmentioning
confidence: 99%
“…The PPI is involved in almost all the important biological processes within the living body and play a crucial role in the fundamental life processes of the cell [30]. Highly aggregated proteins often exhibit similar functions [31], while proteins with a high degree of connectivity may be key points for influencing metabolic reactions [27]. The DEPs in each comparison group were compared with the STRING database, and protein interaction network maps were drawn by screening the proteins with closer interactions (Figures 8-11).…”
Section: Ppi Network Analysis Of Deps In Different Samplesmentioning
confidence: 99%
“…MC regulates a wide range of biological activities in various crops [ 58 ]. In response to abiotic stresses, MC decreased vegetative growth while increasing crop yield in soybean and cotton under drought stress [ 40 , 59 ].…”
Section: Biosynthesis Signaling and Transduction Pathways Of MC And Mtmentioning
confidence: 99%
“…A previous study demonstrated that ABA is the primary hormone that promotes leaf senescence under abiotic stress in different crops [ 128 ]. The content of ABA and its biosynthesis genes gradually increased during leaf senescence in cotton plants [ 58 ]. MT reduced the upregulation of ABA biosynthesis genes, NCED1 and NCED2 , and their accumulation in cotton [ 129 ].…”
Section: MC and Mt Relevant Gene Involved In Cotton Growthmentioning
confidence: 99%
“…The use of MC under salt stress can significantly increase dry weight, fresh weight, glycine betaine content, and proline and phenolic compounds in cotton [ 12 ]. Additionally, MC enhanced the GSH-ASA and Calvin cycles of soybeans during drought stress to lessen oxidative damage and preserve crop development [ 13 ]. Therefore, MC has considerable application potential in the regulation of crop yield and stress resistance.…”
Section: Introductionmentioning
confidence: 99%